3D Modeling and Augmented Reality for Learning - Adel Fridhi; Rim Laribi; Naila Bali (Computational Engineering and Physical Modeling)
Through this article, we propose to provide some answers to these questions. 3D modeling, the concept of augmented reality (AR) and its basis. Innovative pedagogical approaches, the concept of each of the methodologies is briefly explained. And a part that provides the answers expected by this article, explaining how AR contributes to the proper application of each educational approach in the field of architecture and civil engineering (CG). Some examples of AR tools adapted to each pedagogical approach are presented. In order to address these different issues based on a scientific and technological state of the art, our research work focused on the proposal of 3D models to facilitate the creation of augmented reality content in the field of civil engineering. This work also made it possible to set up a experimental environment based on buildings and we chose some example of a building as the first example and New York City as the second example.